未完成的杀戮 ：近期南京大屠杀题材电影研究 = The unfinished killing : a study of recent Nanking massacre cinema - 姚丽宏 Yao, Lihong (2012)
在充满风雨涕零的中国近代史，几乎没有任何一起事件，比之南京大屠杀更加具有持续性的象征意涵。即使在时隔近八十年后的今日，由于其死亡人数之重大以及侵略行为之残暴，中日双方乃至西方社会，从民间到官方的论述，政治宣导的批判延及文化艺术的再现，对于南京大屠杀的研究和讨论，其实仍然历历在目的进行。南京大屠杀于焉也从一个曾经交织着暴戾和屈辱的历史事件，逐渐演变成为意识形态国家机器的工具，用以形塑民族主义意识和建构国民集体记忆之余，同时也不断地被重新诠释和展示，赋予了即时的现实政治色彩。 本持跨领域的研究视野，本论文将以近年来三部南京大屠杀题材的剧情电影：《南京1937》、《南京！南京！》和《金陵十三钗》，作为分析和探讨的核心。将这三部电影的文本置于中国社会历史的语境，通过叙事视角的差异和意识主题的转变，本论文阐述了南京大屠杀如何从历史事件过渡为视觉符号，在中国当代史的社会轨迹里，留下了一道不可磨灭的庞大显影。In the winding and tumultuous period of modern China, none other event has continually garnered as much symbolic significance than the Nanking Massacre, which underlined the suffering and humiliation of Chinese people. Even though the event occurred nearly eight decades ago, due to its incomprehensible scale and brutal nature of the atrocity committed by the invading Japanese troop, both historical scholars and the general public from China, Japan and the Western world, have never ceased their study and interest on this topic. From political propaganda to artistic representation, the Nanking Massacre has evolved into the mechanism of the Ideological State Apparatus, imbued with the collective memory and growing nationalism of the Chinese population. In a way, this past event was constantly being interpreted and reenacted, as to ensure an unyielding political importance. Undertaking an interdisciplinary approach, this dissertation will focus its study on three recent feature films: Don’t Cry, Nanking, City of Life and Death and The Flowers of War. With a similar theme of the Nanking Massacre, these three films constitute the primary basis of this study. Positioning the films in the social and historical context of China, and by comparatively analyzing the differences in narrative perspective and motif, this dissertation shows how the Nanking Massacre transformed itself from a historical event and transfixed into our visual imagination, thus leaving a lasting mark in the development of contemporary Chinese history.